Phenomenological representation of biosociality in female-headed households - Tabrizikahuo, Gholamreza; Salehi, Keyvan; Keshavarz Afshar, Hossein; Madani, Yaser (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The number of Female Headed Households heads of households in Iran is currently increasing; And the general consensus on the issue of their vulnerability has led many studies to unravel their issues. One of the most important, especially in Iran, is the social relations of these women and the expectations that society has of them. The purpose of this research is to study the lived experience of these women in their social relationships. Methods: This research was conducted by phenomenological method. The research fild was the city of Mashhad and the participants were female-headed households in the winter 2022 who were selected by purposive sampling method with maximum distribution. Data were collected through semi-structured interviews which in the 21st case ended with theoretical saturation. Data analysis was performed by Colaizzi method. Results: Female-headed households make changes in their social relationships in the four dimensions of living body, relationships, social space and time before and after household heading. For one group the body is somthing that carries the honor and for another group is a tool to protest the status quo. Lived relationships also fluctuate in a wide range from social distance to complete freedom. They all agree that the social environment is insecure and unreliable for them. Some have a positive attitude towards the past, some have a negative attitude, some try to forget the past and live in the present and some surrender to their destiny, and finally some try to change their lived-world according to their current situation. Conclusion: It is necessary for the support systems of these women to take their social relations seriously and pay attention to all four dimensions of their physical life, social space, communication and time.